2012
DOI: 10.1063/1.4704545
|View full text |Cite
|
Sign up to set email alerts
|

Coordination variation of hydrated Cu2+/Br1− ions traversing the interfacial water in mesopores

Abstract: Resolution of the atomistic and electronic details about the coordination structure variation of hydrated ions in the interfacial water is still a tough challenge, which is, however, essentially important for the understanding of ion adsorption, permeation and other similar processes in aqueous solutions. Here we report the tracing of coordination structure variation for hydrated Cu2+/Br1- ions traversing the interfacial water in Vycor mesopores (ϕ = 7.6 nm) by employing both X-ray absorption near edge structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In addition, the latter study found the extent of cation desolvation to be inversely proportional to the size of the pores. (34) Similarly, classical molecular dynamics simulation on aqueous NaCl (37) and X-ray absorption spectroscopy experiment on aqueous CuBr2 (35) agree about the bulk-like cation-hydration structure in larger pores and the decrease in hydration and enhancement in ion pairing in smaller pores. Moreover, Nelson et al, (36) used Zn K-edge EXAFS to study aqueous Zn(NO3)2, and concluded that Zn 2+ adsorbs in a tetrahedral coordination in nanoporous silica with pores <10 nm whereas the Zn 2+ ions exists instead as a mixture of tetrahedrally and octahedrally coordinated surface complexes for pore size >10 nm.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…In addition, the latter study found the extent of cation desolvation to be inversely proportional to the size of the pores. (34) Similarly, classical molecular dynamics simulation on aqueous NaCl (37) and X-ray absorption spectroscopy experiment on aqueous CuBr2 (35) agree about the bulk-like cation-hydration structure in larger pores and the decrease in hydration and enhancement in ion pairing in smaller pores. Moreover, Nelson et al, (36) used Zn K-edge EXAFS to study aqueous Zn(NO3)2, and concluded that Zn 2+ adsorbs in a tetrahedral coordination in nanoporous silica with pores <10 nm whereas the Zn 2+ ions exists instead as a mixture of tetrahedrally and octahedrally coordinated surface complexes for pore size >10 nm.…”
Section: Introductionmentioning
confidence: 72%
“…It has been proposed that water forms a dense ordered layer on the solid -aqueous solution interface and the ordering can extend up to 6 -7 Å from the wall after which it becomes more diffuse as in the bulk case. (35,37) Such an ordering of water near the interface decreases its dielectric constant and favors ion pairing from an entropic perspective. Further, for NPC with a very large surface area and a very high surface to volume ratio, a large fraction of water molecules in the solution would be consumed in the interfacial layer effectively increasing the concentration of the remaining core solution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[96] The chemistry of EDL, the type of ion adsorbed on the surface of electrodes, and especially the component and the structure of solvation sheath of ions in EDL region determine the formation, chemistry, and structure of SEI. [96][97][98][99][100][101] In 2004, Abe and coworkers first studied the activation energy for the transfer of desolvated Li + at SEI between graphite and electrolyte solutions, i.e., 1 mol/dm 3 LiCF 3 SO 3 dissolved in 1,2-dimethoxyethane (DME) and DMSO, respectively. [102] The measured activation energies ranging from 53 kJ/mol to 59 kJ/mol are about twice as much as that of the solvated Li + transfer in a reference system without stable SEI film, i.e., graphite/LiClO 4 dissolved in mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) (Fig.…”
Section: Transport Behavior Of Ions Through Solid Electrolyte Interfacementioning
confidence: 99%